Reengineering Business Process Manufacturing Company Sales Module Using Odoo V12.0 Application - Wahyuni, Rika Hari; Sukarsa, I Made; Arsa, Dewa Made Sri (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
The manufacturing industry applies the use of ERP to run corporate business  processes, build good communication and improve service quality. This study aims to provide a  Business Process Reengineering proposal to the sales department using the Odoo V12.0 so  that the system can be integrated. The methodology used in this research is Business Process  Reengineering, where the research only focuses on the sales field. Existing business  processes, namely purchasing products, sales orders and invoicing manuall. Reengineering that  has been carried out is the product sales process, the sales order process, and the payment  process. Reengineering has been carried out quite well by using the User Acceptance Test  method and obtaining agreed responses as the greatest value in every aspect. The results  obtained are based on 5 categories, namely content items by 63%, module items by 53%,  multimedia element items by 88%, navigation aspects by 70% and usability items by 82%. Keywords: Business Process Reengineering, Enterprise Resource Planning, Odoo V12.0,  Sales, User Acceptance Test